A systematic review of outcome measures reported for the therapeutic effectiveness of oral anticoagulation. Issue 1 (1st January 2003) - Fitzmaurice, D A; Kesteven, P; Gee, K M; Murray, E T; McManus, R
Abstract : Aims: To evaluate the evidence of therapeutic international normalised ratio (INR) control reporting and to provide recommendations for future reporting, particularly for research and audit purposes. Methods: A systematic review of literature published over a five year period describing therapeutic INR control. Papers were identified from the Medline electronic database, and those that met the quality criteria were reviewed independently by an academic general practitioner and a consultant haematologist. Results: Fifteen papers were identified that met the quality criteria for review. The sample size of studies ranged from 53 to 2545 (mean, 483.9) patients. Follow up ranged from three months to 13 years. Twelve studies reported results from secondary care only, one from primary care only, and two from both primary and secondary care. Seven of the 15 papers reported percentage time in range, five of 15 papers reported mean INR, six of 15 papers reported the proportion of tests in range, and five of 15 papers reported mean warfarin dose. Additional methods of presenting INR results were: dose changes each month, distribution of INR results, deviation of INR value from mean, percentage dose changes, time between visits, and median INR value. Six papers reported only one outcome measure, six reported two outcomes, two papers reported three outcomes, and one paper reported five outcomes. Conclusions: It is recommended that at least two outcome measures should be reported and measures should be selected so that both the INR determinations and dosing advice are monitored.